The efficiency of dynamic relaxation methods in static analysis of cable structures. (November 2015) - Hüttner, M.; Máca, J.; Fajman, P.
Abstract: Nine different schemes of dynamic relaxation method are compared in the paper. Schemes with viscous damping and schemes with kinetic damping are used. Kinetic damping with a peak in the middle of the time step and kinetic damping with the parabolic approximation of the peak are considered. They are also used in three different ways of cable approximation. The cable is approximated as a tension bar, a catenary and a parabolic cable element. The efficiency and stability of each method are compared to three selected 3D examples of cable structures and one existing structure. The effect of mass distribution along the structure is also of interest and is studied in the paper.